The impacts of dollarization on Zimbabwe’s tourism industry - Kabote, F.; Chimutingiza, F.; Mirimi, K. (International Journal of Development and Sustainability, 2013)
The word “dollarization” has been used to describe the adoption of United States Dollar (US$) or other major advanced country’s currency as the currency of choice in a foreign country. Upon adoption in 2009 February, Zimbabweans and the tourism industry were optimistic about the future as they thought it would bring a more stable economy. Three years down the line it is prudent to evaluate and see if this much talked about and praised economic move had any effect on the performance of one key sector of the Zimbabwean economy (Tourism). To answer this question a graphical and quantitative analysis of Zimbabwean Tourism industry performance indicators was done. The data was grouped into pre-2009 and post-2009 and compared the means and variables between these two eras. The results of the analysis lead us to conclude that there is a positive impact of dollarization on the Zimbabwean Tourism industry.